Synthesis of a new class of aminocyclitol analogues with the conduramine D-2 configuration - Kelebekli, Latif; Kara, Yunus; Celik, Murat (Beilstein Journal of Organic Chemistry, 2010)
A new class of aminocyclitol derivatives with the bicyclo[4.2.0]octane skeleton was synthesized starting from cyclooctatetraene. Photooxygenation of trans-7,8-diacetoxy- and cis-7,8-dichlorobicyclo[4.2.0]octa-2,4-diene afforded the bicyclic endoperoxides. Reduction of the latter with thiourea followed by a Pd(0) catalyzed ionization/cyclization reaction gave the corresponding oxazolidinone derivatives. Oxidation of the double bond with KMnO4 or OsO4 followed by acetylation gave the acetate derivatives, the exact configuration of which was determined by spectroscopic methods. Hydrolysis of the oxazolidinone rings and removal of the acetate groups furnished the desired aminocyclitols.
Keywords: aminocyclitol; cyclitols; endoperoxide; oxidation; X-ray analysis